Positive electrode material for sodium-ion batteries, method for its production, positive electrode composition, sodium-ion secondary battery and use
Patent Information
- Application Number
- CN202411776550.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-12-04
AI Technical Summary
[0004]当前O3相高容量的钠离子层状氧化物正极材料技术路线之一是提高材料中的镍元素比例,镍元素电化学活性较高,单个镍原子可在Ni2+/Ni3+/Ni4+价态之间进行切换,为高容量正极材料提供理论基础,但是随着Ni含量的提高,钠离子层状氧化物正极材料往往会生成较为明显的氧化镍杂相,或者生成残碱杂相,不利于电化学性能的发挥,尤其对循环性能造成明显的恶化
[0029]申请人发现,通过控制正极材料的整体组成以及包覆层的组成(以及因此内核的组成,换而言之控制内核和包覆层的组成以及因此正极材料的整体组成),特别是通过在制备内核时将Ni源和Na源以特定的量过量使用,并且然后在形成包覆层时控制包覆层所用Co源与制备内核时过量的Ni源之间的比率,以使得在制备内核时过量的Ni源和Na源被消耗用于包覆层,从而所制备得到的正极材料和包覆层(以及因此内核)具有所限定的组成,由此能够消除常规烧结条件下容易出现的氧化镍杂相,降低残碱含量,和/或改善粉末(电子)电导率;相对于组成在所限定范围之外的正极材料,所得正极材料能够改善初始放电容量和循环性能(尤其是高倍率(例如1C)下的高温循环性能)。
Smart Images

Figure CN119581530B_ABST
Abstract
Description
Technical Field
[0001] This invention relates generally to the field of energy storage technology, particularly to the field of sodium-ion secondary batteries. Specifically, this invention relates to positive electrode materials for sodium-ion batteries, their preparation methods, positive electrode compositions comprising the same, sodium-ion secondary batteries comprising the positive electrode compositions, and the uses of the sodium-ion secondary batteries. Background Technology
[0002] Because sodium ions are abundant and have inexpensive raw materials, sodium-ion rechargeable batteries are considered to be highly likely to replace lithium-ion rechargeable batteries to solve the lithium resource shortage problem, thereby achieving inexpensive large-scale energy storage and large-scale commercial applications.
[0003] However, the large atomic mass of sodium ions results in a lower theoretical capacity for sodium-ion layered oxide cathode materials compared to lithium-ion layered oxide cathode materials, further leading to a lower usable actual energy density. The energy density of sodium-ion layered oxide cathode materials can be improved by adjusting the material system and the combination of elements. The main approaches are: (1) increasing the specific capacity of the active material, and (2) increasing the upper limit of the discharge voltage to utilize more reversible specific capacity and increase the battery operating voltage.
[0004] One of the current technical routes for high-capacity sodium-ion layered oxide cathode materials with O3 phase is to increase the proportion of nickel in the material. Nickel has high electrochemical activity, and a single nickel atom can switch between Ni2+ / Ni3+ / Ni4+ valence states, providing a theoretical basis for high-capacity cathode materials. However, with the increase of Ni content, sodium-ion layered oxide cathode materials often generate more obvious nickel oxide impurity phases or residual alkali impurity phases, which are not conducive to the performance of electrochemical properties, especially causing a significant deterioration in cycle performance.
[0005] Therefore, for layered oxide cathode materials with high nickel content in the O3 phase, it is still necessary to improve their electrochemical performance. Summary of the Invention
[0006] This invention was made in view of the above-mentioned problems existing in the prior art.
[0007] In a first aspect, the present invention relates to a positive electrode material for sodium-ion batteries, comprising:
[0008] A layered oxide core and a layered oxide coating layer formed on the core.
[0009] The cathode material has the following overall composition:
[0010] Na 1+2x Ni u+x(1+y) Co x(1-y) M 1-u O2+δ
[0011] The covering layer is represented by the following formula:
[0012] Na2Ni 1+y Co 1-y A α O 4+β
[0013] And the molar ratio of the coating layer to the core is x.
[0014] in
[0015] x = 0.01 - 0.03,
[0016] u = 0.40 - 0.49,
[0017] y = -0.10 to 0.10,
[0018] M is selected from at least two elements chosen from the metallic elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, and includes Cu and Mn.
[0019] δ = -0.40 to 0.40,
[0020] A is selected from some or all of the elements of M.
[0021] 0 < α < 1,
[0022] 0 < β < 2.
[0023] In a second aspect, the present invention relates to a method for preparing the cathode material of the first aspect, comprising the following steps:
[0024] Core preparation: Na source, Ni source, and M source were mixed uniformly according to the molar ratio of Na, Ni, and M elements of (1+2x):(u+x(1+y)):(1-u), and subjected to a first sintering at a first temperature of 850-1000℃ in an oxygen-containing atmosphere. After cooling, the mixture was optionally pulverized and sieved to obtain the core substrate, wherein the Na source (Na element) and Ni source (Ni element) were in molar excess of 2x and x(1+y) respectively, relative to the stoichiometry of the core composition.
[0025] Preparation of the coating layer: The prepared core substrate and Co source are uniformly mixed according to the molar ratio of excess Ni element to Co element in the core preparation as (1+y) / (1-y). Then, a second sintering is carried out in an oxygen-containing atmosphere at a second temperature of 800-980°C, which is lower than the first temperature. After cooling, the material is optionally crushed and sieved to obtain the cathode material.
[0026] In a third aspect, the present invention relates to a positive electrode composition for sodium-ion secondary batteries, comprising the positive electrode material for sodium-ion batteries of the first aspect of the present invention.
[0027] In a fourth aspect, the present invention relates to sodium-ion secondary batteries comprising the positive electrode composition of the third aspect of the present invention.
[0028] In a fifth aspect, the present invention relates to the use of the sodium-ion secondary battery of the fourth aspect of the present invention in energy storage devices, particularly for energy storage devices used in solar power generation, wind power generation, smart grid peak shaving, distributed power stations, backup power supplies or communication base stations.
[0029] The applicant discovered that by controlling the overall composition of the cathode material and the composition of the coating layer (and thus the composition of the core, in other words, controlling the composition of the core and the coating layer and thus the overall composition of the cathode material), particularly by using Ni and Na sources in excess in specific amounts during core preparation, and then controlling the ratio between the Co source used in the coating layer and the excess Ni source during core preparation, so that the excess Ni and Na sources during core preparation are consumed for the coating layer, the resulting cathode material and coating layer (and thus the core) have a defined composition. This eliminates nickel oxide impurities that are prone to occur under conventional sintering conditions, reduces residual alkali content, and / or improves powder (electronic) conductivity. Compared to cathode materials with compositions outside the defined range, the resulting cathode material improves initial discharge capacity and cycle performance (especially high-temperature cycle performance at high rates (e.g., 1C)). Attached Figure Description
[0030] To more clearly illustrate the technical solution of the present invention, the accompanying drawings required for describing the embodiments will be briefly described below. It should be understood that these drawings are only for the purpose of facilitating a better understanding of the present invention by those skilled in the art, and are not intended to limit the scope of the present invention, wherein:
[0031] Figure 1-3 The images shown are scanning electron microscope (SEM) images of the cathode materials prepared in Examples 1-3 at 10,000x magnification.
[0032] Figure 4 The XRD patterns of the core substrate and the final cathode material after coating prepared in Example 4 are shown.
[0033] Figure 5 The first charge-discharge curve of the cathode material prepared in Example 5 is shown. Detailed Implementation
[0034] To make the inventive objectives, technical solutions, and beneficial technical effects of this application clearer, this application will be described in detail below. It should be noted that the various aspects, features, embodiments, and advantages described in this application can be compatible and / or combined together.
[0035] Unless otherwise specified, the technical terms used in this specification have the same meaning as commonly understood by those skilled in the art.
[0036] Unless otherwise specified, the temperature in this application is room temperature (25°C), the atmosphere is air, and the pressure is atmospheric pressure.
[0037] Those skilled in the art will understand that, unless otherwise specified, in this application, a number containing n significant digits after the decimal point actually also includes the result of rounding a number containing more significant digits after the decimal point to n significant digits. For example, 1.0 actually covers all numbers in the range from greater than or equal to 0.95 to less than 1.05; 0.16 actually covers all numbers in the range from greater than or equal to 0.155 to less than 0.165; 0.166 actually covers all numbers in the range from greater than or equal to 0.1655 to less than 0.1665, and so on.
[0038] This invention relates to a positive electrode material for sodium-ion batteries, a method for preparing the same, a positive electrode composition comprising the same, a sodium-ion secondary battery comprising the positive electrode composition, and the use of the sodium-ion secondary battery.
[0039] The present invention will be described in detail below.
[0040] cathode materials
[0041] In a first aspect, the present invention relates to a positive electrode material for sodium-ion batteries, comprising:
[0042] A layered oxide core and a layered oxide coating layer formed on the core.
[0043] The cathode material has the following overall composition:
[0044] Na 1+2x Ni u+x(1+y) Co x(1-y) M 1-u O 2+δ
[0045] The covering layer is represented by the following formula:
[0046] Na2Ni 1+y Co 1-y A α O 4+β
[0047] And the molar ratio of the coating layer to the core is x.
[0048] in
[0049] x = 0.01 - 0.03,
[0050] u = 0.40 - 0.49,
[0051] y = -0.10 to 0.10,
[0052] M is selected from at least two elements chosen from the metallic elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, and includes Cu and Mn.
[0053] δ = -0.40 to 0.40,
[0054] A is selected from some or all of the elements of M.
[0055] 0 < α < 1,
[0056] 0 < β < 2.
[0057] The applicant discovered that when the cathode material has the defined overall composition and coating composition (and therefore a specific core composition), it is possible to eliminate nickel oxide impurities that are prone to occur under conventional sintering conditions, reduce residual alkali content, and / or improve powder (electronic) conductivity. Compared with cathode materials with compositions outside the defined range, the resulting cathode material can improve initial discharge capacity and cycle performance (especially high-temperature cycle performance at high rates (e.g., 1C)).
[0058] In an embodiment, the molar ratio of the coating layer to the core (i.e., the ratio of the molar amount of the coating layer according to its composition to the molar amount of the core according to the composition obtained by subtracting the composition of the coating layer from the overall composition of the cathode material) x = 0.01-0.03, for example 0.01, 0.02, 0.03, or a range defined by any two thereof. Within the defined range, compared to other ranges (e.g., lower x (including cases with fewer coating layers and cases without coating layers) or higher x), the initial discharge capacity and cycle performance (e.g., high-temperature cycle retention at high rates (e.g., 1C)) of the resulting cathode material can be improved.
[0059] In this embodiment, u = 0.40-0.49; for example, u can be 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, or a range defined by any two thereof. Within the defined range, the resulting cathode material can achieve improved initial discharge capacity and cycle performance (e.g., high-temperature cycle retention at high rates (e.g., 1C)).
[0060] In an implementation, y = -0.10 to 0.10, for example, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; preferably y = -0.05 to 0.05, for example, y = -0.02 to 0.02, for example, 0. Within the defined range (e.g., relative to the case where the coating layer does not contain Na and / or Ni and / or the Ni / Co ratio is outside the range, such as the case where the coating layer contains a lower ratio of Ni, or even does not contain Ni, or contains a higher ratio of Ni), the initial discharge capacity and cycle performance (e.g., high-temperature cycle retention at high rates (e.g., 1C)) of the resulting cathode material can be improved.
[0061] In the embodiments, element M is selected from at least two elements chosen from the metallic elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, and includes Cu and Mn; preferably, M may be selected from at least two elements chosen from the metallic elements Cu, Fe, Mn, Ti, Mg, Zn, Al, Zr, Sn, and Y, and includes Cu and Mn.
[0062] In a preferred embodiment, M includes or is Cu and Mn.
[0063] In a preferred embodiment, M includes or is Cu, Mn and Ti.
[0064] In a preferred embodiment, M includes Cu, Mn, and Ti, and optionally further includes one or more elements selected from Fe, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, preferably one or more elements selected from Fe, Mg, Zn, Al, Zr, Sn, and Y.
[0065] In the implementation, the subscript of element M in the positive electrode material is 1-u, that is, 0.51-0.60, for example 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, or a range defined by any two of them.
[0066] In the implementation, δ = -0.40 to 0.40, for example, -0.40, -0.39, -0.38, -0.37, -0.36, -0.35, -0.34, -0.33, -0.32, -0.31, -0.30, -0.29, -0.28, -0.27, -0.26, -0.25, -0.24, -0.23, -0.22, -0.21, -0.20, -0.19, -0.18, -0.17, -0.16, -0.15, -0.14, -0.13, -0.12, -0.11, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, - 0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, or a range defined by any two of these values.
[0067] In this embodiment, the coating layer includes Na, Ni, and Co elements, and further includes element A. Element A is selected from some or all of the elements M (in terms of element type); preferably, element A is the same as element M (in terms of element type). Preferably, element A comes from element M used in the core preparation process; that is, no additional element A is added during the coating process.
[0068] In the implementation, the subscript α of element A in the coating layer satisfies 0 < α < 1. For example, α can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or 0.2. 1, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range defined by any two of them.
[0069] In this implementation, the subscript β of the O element in the coating layer satisfies chemical equilibrium, and 0 < β < 2. β can vary depending on the valence state and content of the A element in the coating layer; for example, β can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.3 8, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.6 3, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.8 8, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12, 1. 13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.30, 1.31, 1.32, 1.33, 1.34, 1.35, 1.36, 1.37, 1. 38, 1.39, 1.40, 1.41, 1.42, 1.43, 1.44, 1.45, 1.46, 1.47, 1.48, 1.49, 1.50, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59, 1.60, 1.61, 1.62, 1. 63, 1.64, 1.65, 1.66, 1.67, 1.68, 1.69, 1.70, 1.71, 1.72, 1.73, 1.74, 1.75, 1.76, 1.77, 1.78, 1.79, 1.80, 1.81, 1.82, 1.83, 1.84, 1.85, 1.86, 1.87, 1.88, 1.89, 1.90, 1.91, 1.92, 1.93, 1.94, 1.95, 1.96, 1.97, 1.98, 1.99, or a range defined by any two of these values.
[0070] In this embodiment, the sum of the subscripts of Co and Ni in the coating layer is 2, and therefore the ratio of the subscript of the Na element in the coating layer is 1:1.
[0071] The cathode material of this invention did not exhibit nickel oxide impurity peaks in X-ray diffraction (XRD) analysis. In this application, the phrase "no nickel oxide impurity peaks" or "no nickel oxide peaks" means that the diffraction intensity of the nickel oxide peak in XRD is lower than the background noise intensity.
[0072] In an implementation, the kernel may have the following components:
[0073] NaNi u M 1-u-αx O 2+γ
[0074] Where u, α, and x are as defined above;
[0075] γ = -0.40 to 0.40, for example, -0.40, -0.39, -0.38, -0.37, -0.36, -0.35, -0.34, -0.33, -0.32, -0.31, -0.30, -0.29, -0.28, -0.27, -0.26, -0.25, -0.24, -0.23, -0.22, -0.21, -0.20, -0.19, -0.18, -0.17, -0.16, -0.15, -0.14, -0.13, -0.12, -0.11, -0.10, -0.09, -0.08, -0.07, -0.06, -0.05, -0.0 4. -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, or a range defined by any two of these.
[0076] Those skilled in the art will understand that the subscripts of the elements in the cathode material (i.e., x, u, y, δ, α, β, and γ) will satisfy valence balance, so that the cathode material, its core, and its coating layer are electrically neutral as a whole. In this application, including embodiments, the subscripts of oxygen elements (e.g., δ and γ) in the cathode material and its core, even if they are not equal to 2, are sometimes simply written as "2", "2.0", or "2.00", which is also a common way of representing the 0 subscript in the art. However, those skilled in the art will understand that when the subscript of oxygen element is not equal to 2, even if it is written as "2", it actually represents a meaning similar to "2+δ" (e.g., δ = -0.40 to 0.40), and based on the proportion of raw materials used and the valence of the relevant elements in the raw materials, those skilled in the art can understand and easily calculate the actual value represented by the subscript 2 of oxygen element in this case, which is entirely within the capabilities of those skilled in the art.
[0077] Those skilled in the art will understand that the cathode material, core, and coating may also contain other elements at impurity levels, such as cobalt that diffuses from the coating into the core during the formation of the coating. However, since the molar ratio of the coating to the core is low and the diffused cobalt accounts for only a small portion of the cobalt used in preparing the coating, very little cobalt enters the core, and thus the changes in the cobalt content in the coating and the cobalt content in the core are negligible.
[0078] A portion of the M element contained in the core may diffuse into the coating layer during subsequent coating of the core, which is understandable to those skilled in the art. In this application, sometimes for convenience (e.g., in embodiments), the above-described composition of the core, NaNi, is also used (based on the raw material composition used in the initial preparation of the core). u M 1-u-αx O 2+γ Abbreviated as NaNi u M 1- u O2, this does not depart from the scope of the invention; those skilled in the art will understand that the core composition of this notation should actually deduct the portion of M elements diffused into the coating layer, that is, it still represents the aforementioned NaNi. u M 1-u-αx O 2+γ Furthermore, based on the overall composition of the cathode material and the composition of the coating layer, the actual composition of the core can be easily determined.
[0079] In the implementation, the core and the coating layer of the cathode material can both belong to the R-3m space group and have an O3 phase crystal structure.
[0080] In the implementation, the subscript of the M element in the overall composition of the positive electrode material satisfies 1-u, i.e., 0.51-0.60, and / or the subscript of the M element in the composition of the core can satisfy 1-u-αx; under this premise, the positive electrode material can further satisfy one or more of the following conditions:
[0081] When M includes Mn, the subscript of Mn in the overall composition and / or core composition of the cathode material can be independently, for example, 0.30-0.59, 0.40-0.51, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, or a range defined by any two of these; and / or
[0082] When M includes Cu, the subscript of Cu in the overall composition of the cathode material and / or the composition of the core can each independently be 0.01-0.20, for example 0.01-0.10, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or a range defined by any two thereof; and / or
[0083] When M includes Ti, the subscript of Ti in the overall composition and / or core composition of the cathode material can be independently 0.01-0.20, for example 0.01-0.10, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or a range defined by any two thereof; and / or
[0084] When M includes Fe, the subscript of Fe in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0085] When M includes Al, the subscripts of Al in the overall composition of the cathode material and / or the core composition can each be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0086] When M includes Y, the subscript of Y in the overall composition of the cathode material and / or the composition of the core can each independently be 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0087] When M includes Mg, the subscript of Mg in the overall composition of the cathode material and / or the core composition can each independently be 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0088] When M includes Zn, the subscript of Zn in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0089] When M includes Zr, the subscript of Zr in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0090] When M includes Sn, the subscript of Sn in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0091] When M includes Li, the subscript of Li in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0092] When M includes Ca, the subscript of Ca in the overall composition of the cathode material and / or the composition of the core can each independently be 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0093] When M includes Ta, the subscript of Ta in the overall composition of the cathode material and / or the composition of the core can each independently be 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0094] When M includes Mo, the subscript of Mo in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0095] When M includes W, the subscript of W in the overall composition of the cathode material and / or the composition of the core can each independently be 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0096] When M includes La, the subscript of La in the overall composition of the cathode material and / or the composition of the core can each independently be 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0097] When M includes Sr, the subscript of Sr in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0098] When M includes Sb, the subscript of Sb in the overall composition of the cathode material and / or the composition of the core can each independently be 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0099] When M includes Ce, the subscript of Ce in the overall composition and / or core composition of the cathode material can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two thereof; and / or
[0100] When M includes Nb, the subscript of Nb in the overall composition of the cathode material and / or the composition of the core can be independently 0.01-0.10, for example 0.01-0.05, for example 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or a range defined by any two of them.
[0101] The cathode material may have a Dv50 particle size of, for example, 1-100 μm, 5-20 μm, or, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 μm, or a range defined by any two thereof. In this application, unless otherwise specified, particle size D50 refers to the particle size of 50% of the volume of particles in the volumetric cumulative distribution curve that is smaller than the stated particle size value. Particle size can be measured, for example, by laser scattering methods commonly used in the art. For example, it can be measured using a Malvern particle size analyzer commonly used in the art, such as the MASTERSIZER-3000.
[0102] The cathode material may have a residual alkali content of less than 0.5%, for example 0.1-0.5%, for example 0.1-0.4%, for example 0.1, 0.2, 0.3, 0.4, 0.5%, or a range defined by any two thereof.
[0103] By controlling the overall composition of the cathode material and the composition of the coating layer (and thus the composition of the core, in other words, controlling the composition of the core and the coating layer and thus the overall composition of the cathode material), the resulting cathode material exhibits superior electrochemical performance, such as improved initial discharge capacity and improved cycle performance (e.g., high rate (e.g., 1C) and high temperature (e.g., 45°C) cycle characteristics) compared to cathode materials with compositions outside the defined range.
[0104] Preparation method of positive electrode material
[0105] In a second aspect, the present invention provides a method for preparing a positive electrode material for a sodium-ion battery according to the first aspect of the present invention, comprising the following steps:
[0106] Core preparation: Na, Ni, and M sources were mixed uniformly at a molar ratio of (1+2x):(u+x(1+y)):(1-u) for Na, Ni, and M, and subjected to a first sintering at a first temperature of 850-1000°C in an oxygen-containing atmosphere. After cooling, the mixture was optionally pulverized and sieved to obtain the core substrate, wherein the Na and Ni sources were in molar excess of 2x and x(1+y) respectively relative to the stoichiometry of the core composition.
[0107] Preparation of the coating layer: The prepared core substrate and Co source are uniformly mixed according to the molar ratio of excess Ni element to Co element in the core preparation as (1+y) / (1-y). Then, a second sintering is carried out in an oxygen-containing atmosphere at a second temperature of 800-980°C, which is lower than the first temperature. After cooling, the material is optionally crushed and sieved to obtain the cathode material.
[0108] The following will provide a detailed explanation of each step.
[0109] Kernel preparation
[0110] The core can be prepared by the following steps: Na source, Ni source and M source are mixed uniformly according to the molar ratio of Na, Ni and M elements (1+2x):(u+x(1+y)):(1-u), and a first sintering is performed at a first temperature of 850-1000℃ in an oxygen-containing atmosphere. After cooling, the mixture is optionally pulverized and sieved to obtain the core substrate, wherein the Na source and Ni source are in molar excess of 2x and x(1+y) respectively, relative to the stoichiometry of the core composition (relative to the amount of Na in the core (Na subscript is 1)).
[0111] During mixing, the Na and Ni sources are used in excess relative to the stoichiometric composition of the core, and the excess amount corresponds to the Na and Ni elemental composition in the coating layer, i.e., the Na and Ni elements in the coating layer originate from the excess Na and Ni sources here.
[0112] The meanings of x, u, and y are the same as those described above, and will not be repeated here.
[0113] The sodium source used is not particularly limited and can be any sodium-containing compound known to those skilled in the art for preparing cathode materials for sodium-ion secondary batteries. Preferably, the sodium source does not ultimately introduce elements other than those constituting the layered oxide cathode material. The sodium source can be one or more in the form of sodium-containing oxides, hydroxides, salts, etc. In one embodiment, the Na source can be one or more compounds selected from sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide, sodium chloride, sodium sulfate, and sodium oxide.
[0114] The Ni source used is not particularly limited and can be any nickel-containing compound known to those skilled in the art for preparing cathode materials for sodium-ion secondary batteries. Preferably, the nickel source does not ultimately introduce elements other than those constituting the layered oxide cathode material. The metal in the Ni source may contain only metallic Ni, or may contain other metals contained in the core of the cathode material in addition to Ni; in this case, the Ni source may be a composite metal compound. In one embodiment, the Ni source may be one or more compounds selected from: nickel carbonate, nickel nitrate, nickel acetate, nickel oxalate, nickel hydroxide, nickel sulfate, nickel chloride, nickel oxide, nickel manganese hydroxide, and nickel manganese titanium copper carbonate.
[0115] Those skilled in the art will understand that, in this application, "not introducing elements other than those constituting the layered oxide cathode material" means that the other elements were not intentionally introduced, which means that the other elements at the impurity level can be introduced into the cathode material.
[0116] The M source is not particularly limited and can be appropriately selected from any M-containing compound known to those skilled in the art for preparing sodium-ion secondary batteries, depending on the overall composition of the cathode material and the composition of the core. The M source can be provided in the following forms: (1) a compound containing only one metal other than sodium contained in the core of the cathode material (e.g., containing only metals Cu, Mn, or Fe), or (2) a compound containing two or more metals other than sodium contained in the core of the cathode material (i.e., a composite metal compound containing multiple metals); or (3) any combination thereof. Preferably, the M source does not ultimately introduce elements other than those constituting the layered oxide cathode material. The metals contained in the M element can each be provided, for example, in the form of carbonates, nitrates, sulfates, oxalates, acetates, chlorides, hydroxides, or oxides; alternatively or additionally, some or all of them can also be provided in the form of composite metal compounds such as oxides, hydroxides, and / or carbonates.
[0117] For example, the Cu source may be one or more compounds selected from the following: copper carbonate, copper nitrate, copper acetate, copper oxalate, copper hydroxide, copper sulfate, copper chloride, copper oxide, copper carbonate, nickel manganese titanium; when used, the Fe source may be one or more compounds selected from the following: ferric carbonate, ferric nitrate, ferric acetate, ferric oxalate, ferric hydroxide, and ferric oxide; the Mn source may be one or more compounds selected from the following: manganese carbonate, manganese nitrate, manganese acetate, manganese oxalate, manganese hydroxide, manganese sulfate, manganese chloride, and manganese oxide (e.g., manganese dioxide), manganese nickel hydroxide, copper carbonate, nickel manganese titanium; when used, the Ti source may be one or more compounds selected from the following: titanium nitrate, titanium oxalate, titanium hydroxide, titanium sulfate, titanium oxysulfate, titanium chloride, and titanium oxide; when used, the Mg source may be one or more compounds selected from the following: magnesium nitrate, magnesium acetate, magnesium oxalate, magnesium hydroxide, magnesium sulfate, magnesium chloride, magnesium carbonate, and magnesium oxide; when used, the Zn source may be one or more compounds selected from the following: zinc nitrate, zinc acetate, ferric oxalate, ferric oxalate, ferric hydroxide, ferric oxalate ... Zinc carbonate, zinc hydroxide, zinc sulfate, zinc chloride, zinc carbonate, and zinc oxide; when used, the Li source may be one or more compounds selected from the following: lithium nitrate, lithium oxalate, lithium acetate, lithium hydroxide, lithium sulfate, lithium chloride, lithium carbonate, and lithium oxide; when used, the Al source may be one or more compounds selected from the following: aluminum carbonate, aluminum nitrate, aluminum acetate, aluminum oxalate, aluminum hydroxide, and aluminum oxide; when used, the Ca source may be one or more compounds selected from the following: calcium carbonate, calcium nitrate, calcium acetate, calcium oxalate, calcium hydroxide, and calcium oxide; when used, the Zr source may be one or more compounds selected from the following: zirconium carbonate, zirconium nitrate, zirconium acetate, zirconium oxalate, zirconium hydroxide, and zirconium oxide; when used, the Y source may be one or more compounds selected from the following: yttrium carbonate, yttrium nitrate, yttrium acetate, yttrium oxalate, yttrium hydroxide, and yttrium oxide; when used, the La source may be one or more compounds selected from the following: lanthanum carbonate, lanthanum bicarbonate, lanthanum nitrate, lanthanum acetate, lanthanum oxalate, lanthanum hydroxide, and lanthanum oxide.
[0118] The mixing can be carried out by any suitable mixing method known to those skilled in the art, such as dry mixing or wet mixing. The wet mixing can be carried out in the presence of any suitable solvent, such as water or ethanol.
[0119] The oxygen-containing atmosphere is not particularly limited and can be, for example, air, oxygen, or compressed air. The pressure of the oxygen-containing atmosphere is not particularly limited and can be any commonly used pressure, for example, above 0.1 MPa, for example, 0.1-1.0 MPa, for example, 0.3-0.7 MPa. The flow rate of the oxygen-containing atmosphere is not particularly limited and can be, for example, 5-20 L / (min·kg), where kg refers to the mass of the sintered mixture on a dry weight basis.
[0120] The first sintering temperature is 850-1000℃, for example, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000℃, or within the range defined by any two of them.
[0121] There is no particular limitation on the first sintering time, and it can be, for example, 10-48 hours, for example, 10-30 hours, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48 hours, or a range defined by any two of these.
[0122] There is no particular limitation on the heating rate during the first sintering, and it can be, for example, 1-10℃ / min, for example, 2-5℃ / min, for example, it can be within the range defined by 1, 2, 3, 4, 5, 6, 7, 8, 9, 10℃ / min, or any two of them.
[0123] After the first sintering, the material is cooled and optionally pulverized and sieved to obtain the core substrate. The cooling, pulverizing, and sieving can be performed by any suitable means known to those skilled in the art. For example, the cooling can be natural cooling, air cooling, or water cooling. For example, the pulverizing can be air jet milling or mechanical milling.
[0124] The core substrate can be pulverized to a Dv50 particle size of, for example, 1-100 μm, or, for example, 5-20 μm. For example, the D50 particle size can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 μm, or a range defined by any two thereof.
[0125] Preparation of coating layer
[0126] In the preparation step of the coating layer, the prepared core substrate is coated, wherein the core substrate prepared above is uniformly mixed with the Co source according to the molar ratio of excess Ni element to Co element in the core preparation of (1+y) / (1-y), and then a second sintering is performed in an oxygen-containing atmosphere at a second temperature of 800-980°C, which is lower than the first temperature. After cooling, the material is optionally crushed and sieved to obtain the cathode material.
[0127] In this embodiment, the core substrate prepared as described above is uniformly mixed with the Co source at a molar ratio of (1+y) / (1-y) for the excess Ni element and the excess Co element in the core preparation. In the core preparation, the Ni source (Ni element) has a molar excess of x(1+y) relative to the stoichiometry of the core composition; therefore, in this step, the amount of Co element added is x(1-y).
[0128] The meanings of x and y are the same as described above, and will not be repeated here.
[0129] The Co source is not particularly limited and can be any cobalt-containing compound known to those skilled in the art for preparing cathode materials for sodium-ion secondary batteries. In one embodiment, the cobalt source can be one or more compounds selected from the following: cobalt carbonate, cobalt nitrate, cobalt acetate, cobalt oxalate, cobalt hydroxide, cobalt sulfate, cobalt chloride, and cobalt oxide.
[0130] The oxygen-containing atmosphere is not particularly limited and can be, for example, air, oxygen, or compressed air. The pressure of the oxygen-containing atmosphere is not particularly limited and can be any commonly used pressure, for example, above 0.1 MPa, for example, 0.1-1.0 MPa, for example, 0.15-0.5 MPa. The flow rate of the oxygen-containing atmosphere is not particularly limited and can be, for example, 5-20 L / (min·kg), where kg refers to the mass of the sintered mixture on a dry weight basis.
[0131] The second temperature is lower than the first temperature. For example, the second temperature may be 10-200°C lower than the first temperature, such as 10-150°C, such as 20-100°C, such as 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200°C lower, or a range defined by any two of these.
[0132] The second temperature can be 800-980℃, for example 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980℃, or a range defined by any two of them.
[0133] There is no particular limitation on the second sintering time, and it can be 10-48 hours, for example 10-30 hours, for example 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48 hours, or a range defined by any two of these.
[0134] There is no particular limitation on the heating rate during the second sintering, and it can be, for example, 1-10℃ / min, for example, 2-5℃ / min, for example, it can be within the range defined by 1, 2, 3, 4, 5, 6, 7, 8, 9, 10℃ / min, or any two of them.
[0135] After the second sintering, the material is cooled and optionally pulverized and sieved to obtain the cathode material. The cooling, pulverizing, and sieving can be performed by any suitable means known to those skilled in the art. For example, the cooling can be natural cooling, air cooling, or water cooling. For example, the pulverizing can be air jet milling or mechanical milling.
[0136] The positive electrode material can be pulverized to a Dv50 particle size of, for example, 1-100 μm or 5-20 μm. For example, the D50 particle size can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 μm, or a range defined by any two of these.
[0137] By using Ni and Na sources in specific excess amounts during core preparation, and then controlling the ratio between the Co source used in the coating layer and the excess Ni source during core preparation during coating layer formation, the excess Ni and Na sources during core preparation are consumed for the coating layer. This results in a defined composition for the core and coating layer of the prepared cathode material. This eliminates nickel oxide impurities that are prone to occur under conventional sintering conditions, reduces residual alkali content, and / or improves powder (electronic) conductivity. Compared to cathode materials with compositions outside the defined range, the resulting cathode material improves initial discharge capacity and cycle performance (especially high-temperature cycle performance at high rates (e.g., 1C)).
[0138] All descriptions above regarding the cathode material of the first aspect of the present invention are applicable here.
[0139] Positive electrode composition
[0140] A third aspect of the present invention provides a positive electrode composition for use in sodium-ion secondary batteries, comprising a positive electrode material for sodium-ion batteries according to a first aspect of the present invention or a positive electrode material for sodium-ion batteries prepared by a method according to a second aspect of the present invention.
[0141] In addition to the cathode material of the present invention, the cathode composition for sodium-ion secondary batteries may also include conductive agents, binders, and any other substances that may be used by those skilled in the art as needed, such as dispersants and additives for improving stability.
[0142] In some embodiments, based on the dry weight of the positive electrode composition for sodium-ion secondary batteries, the content of the positive electrode material can be a commonly used amount in the art, for example, 70-95% by weight, or, for example, 80-90% by weight.
[0143] There are no particular limitations on the type of conductive agent, as long as it enhances the conductivity of the positive electrode and does not adversely affect the performance of the positive electrode material. Those skilled in the art can select conductive agents commonly used in the art according to actual needs. As an example, the conductive agent used in the aforementioned positive electrode composition for sodium-ion secondary batteries may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0144] In some embodiments, based on the dry weight of the positive electrode composition for sodium-ion secondary batteries, the content of the conductive agent may be a commonly used amount in the art, for example, 1-10% by weight, or, for example, 2-5% by weight.
[0145] There are no particular limitations on the binder, as long as it enhances the adhesion between the positive electrode active material particles and the adhesion to the current collector, and does not adversely affect the performance of the positive electrode material. Those skilled in the art can select according to actual needs. As an example, the binder used in the positive electrode composition for the sodium-ion secondary battery can be selected from polyfluoroolefin binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), or their modified (e.g., modified with carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives, as well as one or more of styrene-butadiene rubber, acrylic resin, carboxymethyl cellulose, polyvinyl alcohol (PVA), etc.
[0146] In some embodiments, the binder content is 1-10% by weight, for example 2-5% by weight, based on the dry weight of the positive electrode composition for the sodium-ion secondary battery.
[0147] The positive electrode composition may be in slurry form, meaning it may further include a solvent. The positive electrode composition may also be in dry form, meaning it does not include a solvent, for example, it may be in the form of a layer of positive electrode active material disposed on a positive electrode current collector.
[0148] Sodium-ion secondary batteries
[0149] A fourth aspect of the present invention provides a sodium-ion secondary battery. A sodium-ion secondary battery typically includes a positive electrode, a negative electrode, a separator, and an electrolyte.
[0150] In some embodiments, the sodium-ion secondary battery may also include an outer packaging for encapsulating the electrode assembly and electrolyte. For example, the outer packaging may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc., or it may be a soft pack, such as a pouch, for example a soft pack made of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0151] There are no particular restrictions on the shape of sodium-ion secondary batteries; they can be cylindrical, square, or any other shape.
[0152] Sodium-ion secondary batteries can be prepared by methods commonly used in the art, for example, by forming a cell from positive electrode, negative electrode and separator through a winding process or a stacking process, and then injecting an electrolyte.
[0153] positive electrode
[0154] The positive electrode (or positive electrode sheet) includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising, for example, a dry form of the positive active material composition of the third aspect of the present invention. The positive electrode also forms an aspect of the present invention.
[0155] There are no particular limitations on the positive electrode current collector, and any positive electrode current collector commonly used by those skilled in the art can be used. As an example, the positive electrode current collector can be a metal foil such as aluminum foil, nickel foil, or a composite current collector. Composite current collectors can be formed by forming a metallic material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), 1,3-propanesulfonate lactone (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0156] The positive electrode sheet can be prepared according to methods commonly used in this field.
[0157] For example, the positive electrode can be formed by uniformly dispersing the positive electrode active material, conductive agent, and binder in a solvent (e.g., N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; coating the slurry onto a positive electrode current collector, drying, and pressing.
[0158] Alternatively, the positive electrode can also be formed by uniformly dispersing the positive electrode active material, conductive agent, and binder in a solvent (e.g., N-methylpyrrolidone (NMP)) to obtain a positive electrode slurry; casting the positive electrode slurry on a separate carrier, drying it, separating the resulting positive electrode film from the carrier, and laminating it onto the positive electrode current collector.
[0159] negative electrode
[0160] The negative electrode (or negative electrode sheet) can be a sodium metal sheet or other commonly used negative electrodes, such as a negative electrode including a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0161] There are no particular limitations on the negative electrode current collector, and any negative electrode current collector commonly used by those skilled in the art can be used. As an example, the negative electrode current collector can be a metal foil such as copper foil, or a composite current collector. The composite current collector may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys, etc.) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.), but the present invention is not limited to these materials.
[0162] In some embodiments, the negative electrode active material may be an active material commonly used by those skilled in the art. For example, the negative electrode active material may be one or more of hard carbon, soft carbon, silicon-based materials, tin-based materials, sodium titanate, and metallic sodium. Among them, the silicon-based material may be one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys, and the tin-based material may be one or more of elemental tin, tin oxide compounds, and tin alloys.
[0163] In addition to the negative electrode active material, the negative electrode active material layer may also include binders, conductive agents, and any other optional additives such as thickeners.
[0164] There are no special requirements for the negative electrode conductive agent. As an example, the conductive agent may be selected from one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0165] In some embodiments, the content of the conductive agent may be 1 to 10% by weight, for example 2-5% by weight, based on the total weight (dry weight) of the negative electrode active material layer.
[0166] There are no special requirements for the negative electrode binder. As an example, the binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), styrene-butadiene rubber (SBR), waterborne acrylic resin, and carboxymethyl cellulose (CMC).
[0167] In some embodiments, the binder content may be 1 to 10% by weight, for example 2-5% by weight, based on the total weight (dry weight) of the negative electrode active material layer.
[0168] The negative electrode can be prepared according to methods commonly used in the art.
[0169] For example, the negative electrode can be formed by uniformly dispersing the negative electrode active material and optionally a conductive agent, binder and thickener in a solvent (e.g. N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, drying and pressing.
[0170] Alternatively, the negative electrode can also be formed by uniformly dispersing the negative electrode active material and optionally a conductive agent, binder and thickener in a solvent (e.g. N-methylpyrrolidone (NMP) or deionized water) to form a negative electrode slurry; casting the negative electrode slurry on a separate carrier, drying it, separating the resulting negative electrode film from the carrier and laminating it onto a negative electrode current collector.
[0171] electrolytes
[0172] The electrolyte acts as a conductor of ions between the positive and negative electrodes. There are no particular limitations on the electrolyte, and it can be selected according to requirements. For example, the electrolyte can be selected from at least one of solid electrolytes, gel electrolytes, and liquid electrolytes (i.e., electrolyte solutions).
[0173] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution comprises an organic aprotic solvent and an electrolyte sodium salt.
[0174] In some embodiments, the solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0175] In some embodiments, the electrolyte sodium salt may be selected from one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroborate (NaBF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), sodium di(oxalate borate) (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorodi(oxalate phosphate) (NaDFOP), and sodium tetrafluorooxalate phosphate (NaTFOP).
[0176] In some embodiments, the concentration of sodium ions in the electrolyte may be 0.2 to 2 mol / L, for example 0.5-1.0 mol / L.
[0177] In some embodiments, the electrolyte may optionally include additives. As an example, the additives may include those that aid in the formation of a negative electrode film or a positive electrode film, and may also include additives that improve battery performance, such as those that improve the battery's high-temperature or low-temperature performance.
[0178] diaphragm
[0179] There are no particular limitations on the membrane, and commonly used porous membranes with electrochemical and chemical stability can be used, such as single-layer or multi-layer films made of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. When using a solid electrolyte, the membrane can also be omitted.
[0180] use
[0181] The fifth aspect of the invention provides the use of sodium-ion secondary batteries according to the fourth aspect of the invention in energy storage devices, particularly for energy storage devices used in solar power generation, wind power generation, smart grid peak shaving, distributed power stations, backup power supplies or communication base stations.
[0182] Those skilled in the art will understand that the sodium-ion secondary battery of the fourth aspect of the present invention can also be used for other purposes. For example, the sodium-ion secondary battery can be used as a power supply or energy storage unit in mobile devices (e.g., mobile phones), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, electric bicycles, electric scooters, etc.), electric trains, etc.
[0183] Example
[0184] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0185] I. Testing Methods
[0186] 1. Residual alkali (Na%) test:
[0187] According to the mass ratio of positive electrode material to ethanol (analytical grade, density 0.789 g / ml) = 1:20, an appropriate amount of positive electrode material (mass denoted as b) was added to the corresponding amount of ethanol. The mixture was magnetically stirred at 600 ± 20 r / min for 30 min to ensure that the ethanol fully dissolves the NaOH and Na₂CO₃ on the surface of the material. The mixture was then filtered to obtain the filtrate. The Na₂CO₃ content in the filtrate was measured using an atomic absorption spectrophotometer (Hitachi ZA3000). + The residual Na content (denoted as a, mg / ml) is calculated using the following formula:
[0188] Residual Na content = (a*(20*b / 0.789)) / b = a*20 / 0.789*1000mg / kg (i.e. ppm).
[0189] The results are converted into percentage content to obtain the residual alkali content based on the total weight of the cathode material.
[0190] 2. Scanning Electron Microscopy-X-ray Energy Dispersive Spectrometer (SEM-EDS)
[0191] The tests were conducted using a Hitachi S-4800 scanning electron microscope-X-ray energy dispersive spectrometer, with an accelerating voltage of 10kV and a magnification of 10k. General morphology images were taken, and the elemental composition of the material surface was analyzed.
[0192] 3. XRD diffraction
[0193] X-ray diffractometer (model Bruker D8 ADVANCE) was used with a copper target (Cu-Kα) (accelerating voltage 40 kV, current 40 mA) for measurements (λ = 1.54056 nm), ranging from 10 to 80 degrees, with a step size of 0.02 degrees, a time of 0.2 s, and a total duration of 712 seconds. The standard PDF card for nickel oxide was referenced in PDF #47-1049.
[0194] 4. Powder conductivity test:
[0195] The powder resistivity was measured using a powder resistivity meter (Guangzhou Sanhao Instrument Co., Ltd., model: eLiPMS-3000Plus) with the following parameters: 4 probes, electrode spacing 2.5 mm, electrode radius 6.5 mm, sample radius 6.5 mm, sample mass 2 g, and the powder resistivity was obtained by holding the pressure at 120 MPa for 3 seconds.
[0196] 5. Dv50 particle size test
[0197] The test was conducted using a Malvern 3000 laser particle size analyzer. Lithium cobalt oxide was selected as the standard substance, and water was used as the dispersant. The instrument test parameters were set as follows: test time 10s, test count 3, occlusion 6-15%, stirring speed 2800r / min, ultrasonic mode on, power 50%. The test was started by clicking the laser particle size analyzer (Malvern 3000 laser particle size analyzer). Then, the first sintered product or cathode material was added to the sample cell, and the occlusion of the sample cell was adjusted to 6-15% by controlling the amount added. The instrument automatically repeated the test 3 times, and the average value of the 3 tests was taken as the mean test result.
[0198] 6. Electrochemical performance testing
[0199] The positive electrode material to be tested, SP (Swiss Temi high-conductivity carbon black SUPER P), polyvinylidene fluoride (PVDF) (PVDF5130 purchased from SOLVAY) and a 10% by mass ratio of N-methylpyrrolidone (NMP) were mixed in a 90:5:5 mass ratio on a dry weight basis. NMP was added to prepare a viscous adhesive. This adhesive was then coated onto an aluminum foil (16 μm thick) and baked in a vacuum drying oven at 120°C for 12 hours to obtain the positive electrode sheet (active material areal density 5 mg / cm³). 2 A sodium metal sheet (Aladdin) was used as the counter electrode (thickness 300±50μm). A glass fiber (Waterman) membrane (thickness 675μm) was used as the separator, and a NaPF6 solution with a sodium ion concentration of 1mol / L (solvent is a mixture of EC and DMC, volume ratio EC / DMC=1:1) (Alfa) was used as the electrolyte. The 2032 coin cell was assembled in an Ar atmosphere-protected glove box.
[0200] For the prepared coin cells, under room temperature (25℃) conditions, they were charged and discharged at a rate of 0.1C within a voltage range of 2.0-4.3V to obtain the initial discharge capacity at 0.1C (unit: mAh / g). Then, using a 45℃ constant temperature coin cell test chamber, they were charged and discharged at a current of 1C within a voltage range of 2.0-4.3V. After each discharge, the cells were allowed to rest for 2 minutes, and the charging and discharging process was repeated for 100 cycles. The ratio of the 100th discharge capacity at 1C rate to the first discharge capacity at 1C rate was calculated as the capacity retention rate after 100 cycles at 45℃.
[0201] II. Example: Preparation of Cathode Material
[0202] Example 1
[0203] Core substrate preparation steps (1): Sodium carbonate, nickel hydroxide, manganese dioxide and cuprous oxide are weighed according to the molar ratio of Na, Ni, Mn and Cu of 1.04:0.42:0.51:0.09, that is, according to the ratio of Na and Ni in excess of 0.04 and 0.02 moles respectively (x=0.02 and y=0) based on Na. All raw materials are thoroughly mixed and calcined at 950℃ under 0.5MPa compressed air for 15h. The core substrate is then prepared by crushing and sieving.
[0204] Coating preparation step (2): Weigh out the coating agent cobalt hydroxide and the core substrate prepared in step (1) according to a molar ratio of Co to the excess Ni in step (1) of 1:1, and mix them thoroughly. Calcinate at 900℃ under 0.5MPa compressed air for 15h. After crushing and sieving, obtain the positive electrode material with a Dv50 particle size of 8.5μm and an overall composition of Na. 1.04 Ni 0.42 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.40 Mn 0.51 Cu 0.09 O2.
[0205] Example 2
[0206] Core substrate preparation steps (1): Sodium carbonate, nickel-manganese hydroxide, and Ni are weighed according to the molar ratio of Na, Ni, Mn, Cu, and Ti of 1.06:0.48:0.45:0.05:0.05, that is, according to the ratio of Na and Ni in excess of 0.06 and 0.03 moles respectively (x = 0.03 and y = 0) relative to Na. 0.5 Mn 0.5 (OH)2, nickel hydroxide, copper hydroxide, and titanium dioxide were thoroughly mixed and calcined at 1000°C under 0.5 MPa compressed air for 10 hours. The resulting material was then pulverized and sieved to obtain the core substrate.
[0207] Coating preparation step (2): Weigh out the cobalt hydroxide coating agent and the core substrate prepared in step (1) according to the molar ratio of Co to the excess Ni in step (1) of 1:1, and mix them thoroughly. Calcinate at 980℃ under 0.5MPa compressed air for 10h. After crushing and sieving, obtain the positive electrode material with a Dv50 particle size of 10.6μm and an overall composition of Na. 1.06 Ni 0.48 Mn0.45 Cu 0.05 Ti 0.05 Co 0.03 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.03, and the core composition can be approximately represented as NaNi. 0.45 Mn 0.45 Cu 0.05 Ti 0.05 O2.
[0208] Example 3
[0209] Core substrate preparation steps (1): Sodium carbonate, copper carbonate, nickel manganese titanium carbonate, and Cu are weighed according to the molar ratio of Na, Ni, Mn, Ti, and Cu as 1.04:0.51:0.40:0.10:0.01, that is, Na and Ni are in excess by 0.04 and 0.02 moles respectively (x = 0.02 and y = 0) relative to Na. 0.01 Ni 0.49 Mn 0.40 Ti 0.10 CO3 and nickel hydroxide were thoroughly mixed, and the mixture was calcined at 900°C under 0.5 MPa compressed air for 20 hours. The resulting material was then pulverized and sieved to obtain the core substrate.
[0210] Coating preparation step (2): Weigh out the coating agent cobalt hydroxide and the core substrate prepared in step (1) according to the molar ratio of Co to the excess Ni in step (1) of 1:1, and mix them thoroughly. Calcinate at 850℃ under 0.5MPa compressed air for 20h. After crushing and sieving, obtain the positive electrode material with a Dv50 particle size of 9.3μm and an overall composition of Na. 1.04 Ni 0.51 Mn 0.40 Ti 0.10 Cu 0.01 Co 0.02 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.49 Mn 0.40 Ti 0.10 Cu 0.01 O2.
[0211] Example 4
[0212] Core substrate preparation steps (1): Sodium carbonate, nickel-manganese hydroxide, and Ni are weighed according to the molar ratio of Na, Ni, Mn, Cu, and Ti of 1.02:0.41:0.40:0.10:0.10, that is, according to the ratio of Na and Ni in excess of 0.02 and 0.01 moles respectively relative to Na (x = 0.01 and y = 0). 0.50 Mn 0.5 (OH)2, nickel hydroxide, copper oxide, and titanium dioxide were thoroughly mixed and calcined at 850°C under 0.5 MPa compressed air for 28 hours. The resulting material was then pulverized and sieved to obtain the core substrate.
[0213] Coating preparation step (2): Weigh out the cobalt hydroxide coating agent and the core substrate prepared in step (1) according to the molar ratio of Co to the excess Ni in step (1) of 1:1, and mix them thoroughly. Calcinate at 800℃ under 0.5MPa compressed air for 28h. After crushing and sieving, obtain the positive electrode material with a Dv50 particle size of 6.4μm and an overall composition of Na. 1.02 Ni 0.41 Mn 0.4 0Cu 0.10 Ti 0.10 Co 0.01 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.01, and the core composition can be approximately represented as NaNi. 0.40 Mn 0.40 Cu 0.10 Ti 0.10 O2.
[0214] Example 5
[0215] Core substrate preparation steps (1): According to the molar ratio of Na, Ni, Mn, Cu, Ti, Fe, Al, Y, Mg, Zn, Zr and Sn is 1.02:0.41:0.40:0.05:0.05:0.04:0.01:0.01:0.01:0.01:0.01, that is, according to the ratio of Na and Ni in excess of 0.02 and 0.01 moles respectively relative to Na (x=0.01 and y=0), sodium carbonate and nickel manganese hydroxide Ni are weighed. 0.50 Mn 0.5 The core substrate is prepared by thoroughly mixing (OH)2, nickel hydroxide, copper oxide, titanium dioxide, ferric oxide, aluminum hydroxide, yttrium oxide, magnesium carbonate, zinc oxide, zirconium dioxide, and tin dioxide, and calcining at 900°C under 0.5 MPa compressed air for 15 hours. The mixture is then pulverized and sieved.
[0216] Coating preparation step (2): Weigh out the cobalt hydroxide coating agent and the core substrate prepared in step (1) according to the molar ratio of Co to the excess Ni in step (1) of 1:1, and mix them thoroughly. Calcinate at 800℃ under 0.5MPa compressed air for 15h. After crushing and sieving, obtain the positive electrode material with a Dv50 particle size of 8.8μm and an overall composition of Na. 1.02 Ni 0.41 Mn 0.4 0Cu 0.05 Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 Co 0.01 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, and the kernel composition can be approximated as NaNi 0.40 Mn 0.40 Cu 0.05 Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 O2.
[0217] Example 6
[0218] The cathode material was prepared in a manner similar to that of Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to the molar ratio of Na, Ni, Mn, and Cu of 1.04:0.422:0.51:0.09, that is, according to the ratio of Na and Ni in excess of 0.04 and 0.022 moles respectively relative to Na (x = 0.02 and y = 0.1); and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to the molar ratio of Co to the excess Ni in step (1) of 1.1:0.9.
[0219] The overall composition of the prepared cathode material is Na 1.04 Ni 0.422 Mn 0.51 Cu 0.09 Co 0.018 O 2+δ The coating layer is composed of Na2Ni1.1 Co 0.9 N α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.40 Mn 0.51 Cu 0.09 O2.
[0220] Example 7
[0221] The cathode material was prepared in a manner similar to that of Example 1, except that: in the core substrate preparation step (1): sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to the molar ratio of Na, Ni, Mn, and Cu of 1.04:0.418:0.51:0.09, that is, according to the ratio of Na and Ni in excess of 0.04 and 0.018 moles respectively relative to Na (x = 0.02 and y = -0.1); and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to the molar ratio of Co to the excess Ni in step (1) of 0.9:1.1.
[0222] The overall composition of the prepared cathode material is Na 1.04 Ni 0.418 Mn 0.51 Cu 0.09 Co 0.022 O 2+δ The coating layer is composed of Na2Ni 0.9 Co 1.1 N α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.40 Mn 0.51 Cu 0.09 O2.
[0223] Comparative Example 1
[0224] The cathode material was prepared in a manner similar to that of Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide and cuprous oxide were weighed according to the molar ratio of Na, Ni, Mn and Cu of 1.04:0.41:0.51:0.10, that is, according to the ratio of Na and Ni in excess of 0.04 and 0.02 moles respectively relative to Na (x = 0.02 and y = 0).
[0225] The overall composition of the prepared cathode material is Na 1.04 Ni 0.42 Mn 0.51 Cu0.10 Co 0.02 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.39 Mn 0.51 Cu 0.10 O2.
[0226] Comparative Example 2
[0227] The cathode material was prepared in the same manner as in Example 2, except that: in the core substrate preparation step (1), sodium carbonate, nickel-manganese hydroxide, and Ni were weighed according to the molar ratio of Na, Ni, Mn, Cu, and Ti of 1.08:0.49:0.45:0.05:0.05, that is, according to the ratio of Na and Ni in excess of 0.08 and 0.04 moles respectively relative to Na (x = 0.04 and y = 0). 0.5 Mn 0.5 (OH)2, nickel hydroxide, copper hydroxide, and titanium dioxide.
[0228] The prepared cathode material has a Dv50 particle size of 10.7 μm and its overall composition is Na. 1.08 Ni 0.49 Mn 0.45 Cu 0.05 Ti 0.05 Co 0.04 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.04, and the core composition can be approximately represented as NaNi. 0.45 Mn 0.45 Cu 0.05 Ti 0.05 O2.
[0229] Comparative Example 3
[0230] The cathode material was prepared in the same manner as in Example 3, except that: in the core substrate preparation step (1), no Cu source was added, and sodium carbonate, nickel hydroxide, manganese dioxide and titanium dioxide were weighed according to the molar ratio of Na, Ni, Mn and Ti of 1.04:0.52:0.40:0.10, that is, according to the ratio of Na and Ni in excess of 0.04 and 0.02 moles respectively relative to Na (x = 0.02 and y = 0).
[0231] The prepared cathode material has a Dv50 particle size of 9.2 μm and its overall composition is Na.1.04 Ni 0.52 Mn 0.40 Ti 0.1 0Co 0.02 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.50 Mn 0.40 Ti 0.10 O2.
[0232] Comparative Example 4
[0233] The cathode material was prepared in the same manner as in Example 4, except that: in the core substrate preparation step (1), sodium carbonate, nickel-manganese hydroxide, and Ni were weighed according to the molar ratio of Na, Ni, Mn, Cu, and Ti of 1.01:0.405:0.40:0.10:0.10, that is, according to the ratio of Na and Ni in excess of 0.01 and 0.005 moles respectively relative to Na (x = 0.005 and y = 0). 0.50 Mn 0.5 (OH)2, nickel hydroxide, copper oxide, and titanium dioxide.
[0234] The prepared cathode material has a Dv50 particle size of 6.4 μm and its overall composition is Na. 1.01 Ni 0.405 Mn 0.40 Cu 0.10 Ti 0.10 Co 0.005 O 2+δ The coating layer is composed of Na2NiCoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.005, and the core composition can be approximately represented as NaNi. 0.40 Mn 0.40 Cu 0.10 Ti 0.10 O2.
[0235] Comparative Example 5
[0236] The cathode material was prepared in the same manner as in Example 5, except that in the coating preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to a molar ratio of Co to Ni in the excess portion of step (1) of 0.8:1.
[0237] The prepared cathode material has a Dv50 particle size of 8.9 μm and its overall composition is Na. 1.02 Ni0.41 Mn 0.40 Cu 0.0 5Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 Co 0.008 O 2+δ The coating layer is composed of Na2NiCo. 0.8 N α O 4+β Where 0 < α < 1, 0 < β < 2, and the kernel composition can be approximated as NaNi 0.40 Mn 0.40 Cu 0.05 Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 O2.
[0238] Comparative Example 6
[0239] The cathode material was prepared in the same manner as in Example 5, except that: in the coating preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to a molar ratio of Co to the excess Ni in step (1) of 1.2:1.
[0240] The prepared cathode material has a Dv50 particle size of 8.5 μm and its overall composition is Na. 1.02 Ni 0.41 Mn 0.40 Cu 0.0 5Ti 0.05 Fe 0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 Co 0.012 O 2+δ The coating layer is composed of Na2NiCo. 1.2 N α O 4+β Where 0 < α < 1, 0 < β < 2, and the kernel composition can be approximated as NaNi 0.40 Mn 0.40 Cu 0.05 Ti 0.05 Fe0.04 Al 0.01 Y 0.01 Mg 0.01 Zn 0.01 Zr 0.01 Sn 0.01 O2.
[0241] Comparative Example 7
[0242] The cathode material was prepared in the same manner as in Example 1, except that: in the substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide and cuprous oxide were weighed according to the molar ratio of Na, Ni, Mn and Cu of 1:0.40:0.51:0.09, that is, according to the ratio of Na and Ni not being excessive relative to Na (x=0); and in the coating layer preparation step (2), no cobalt source was added (i.e. no coating was performed) and only sintering was performed.
[0243] The prepared cathode material has a Dv50 particle size of 10.5 μm and a composition of NaNi. 0.40 Mn 0.51 Cu 0.09 O2.
[0244] Comparative Example 8
[0245] The cathode material was prepared in the same manner as in Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to the molar ratio of Na, Ni, Mn, and Cu of 1:0.40:0.51:0.09, that is, according to the ratio of Na and Ni not being excessive relative to Na (x=0); and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to the molar ratio of Co to the core substrate prepared in step (1) (i.e., the amount of Na element used in step (1)) of 0.02.
[0246] The prepared cathode material has a Dv50 particle size of 10.3 μm and an overall composition of NaNi. 0.40 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ The coating layer is composed of CoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.40 Mn 0.51 Cu 0.09 O2.
[0247] Comparative Example 9
[0248] The cathode material was prepared in the same manner as in Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to the molar ratio of Na, Ni, Mn, and Cu of 1:0.42:0.51:0.09, that is, according to the ratio of Na not being excessive and Ni being molarly excessive by 0.02 relative to Na; and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to the molar ratio of Co to the core substrate prepared in step (1) (i.e., the amount of Na element used in step (1)) of 0.02.
[0249] The prepared cathode material has a Dv50 particle size of 10.6 μm and its overall composition is NaNi. 0.42 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ The coating layer is composed of CoNiN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.40 Mn 0.51 Cu 0.09 O2.
[0250] Comparative Example 10
[0251] The cathode material was prepared in the same manner as in Example 1, except that: in the core substrate preparation step (1), sodium carbonate, nickel hydroxide, manganese dioxide, and cuprous oxide were weighed according to the molar ratio of Na, Ni, Mn, and Cu of 1.04:0.40:0.51:0.09, that is, according to the ratio of Na molar excess of 0.04 relative to Na and Ni not excess; and in the coating layer preparation step (2), the coating agent cobalt hydroxide and the core substrate prepared in step (1) were weighed according to the molar ratio of Co to the core substrate prepared in step (1) (i.e. the amount of Na element used in step (1)) of 0.02.
[0252] The prepared cathode material has a Dv50 particle size of 10.6 μm and its overall composition is Na. 1.04 Ni 0.40 Mn 0.51 Cu 0.09 Co 0.02 O 2+δ The coating layer is composed of Na2CoN α O 4+β Where 0 < α < 1, 0 < β < 2, the molar ratio of the coating layer to the core is 0.02, and the core composition can be approximately represented as NaNi. 0.40 Mn0.51 Cu 0.09 O2.
[0253] Figure 1-3 Scanning electron microscope (SEM) images of the cathode materials prepared in Examples 1-3 at 10,000x magnification are shown respectively, which clearly show that coating has occurred in the obtained cathode materials.
[0254] Figure 4 The XRD patterns of the core substrate and the final cathode material prepared in Example 4 are shown. Based on the XRD standard card: PDF#54-0887 (O3 phase), from... Figure 4 It can be seen that the main body of the material is O3 phase (that is, both the core and the coating layer are O3 phase structures). The difference between the two is that the core substrate shows NiO impurity peaks before coating, while there are no NiO impurity peaks after coating.
[0255] Figure 5 The first charge-discharge curve of the cathode material prepared in Example 5 at 0.1C rate at room temperature is shown, which shows a relatively flat charge-discharge plateau behavior.
[0256] The properties of the cathode materials prepared in Examples 1-7 and Comparative Examples 1-10 are shown in Table 1 below.
[0257] As can be seen from Table 1, in the preparation of the core substrate in Examples 1-7, excess nickel source and excess sodium source were used. The core substrates obtained all had obvious nickel oxide impurity peaks and high residual alkali content (all greater than 0.5%), indicating that the excess nickel and sodium existed on the material surface in the form of impurity phases. After adding cobalt source for secondary calcination coating, the NiO impurity peaks in the obtained cathode material disappeared, and the residual alkali content was significantly reduced (all not greater than 0.31%), indicating that Co consumed NiO and residual alkali Na at the same time. In contrast, Comparative Example 7 did not use excessive amounts of sodium and nickel during the first calcination. As a result, although it showed a relatively low residual alkali content (0.376%) after the first calcination, it still exhibited the Ni impurity phase. After the second calcination, the NiO impurity peak disappeared, but the residual alkali content increased slightly to 0.395%. In Comparative Example 10, nickel was not used excessively and sodium was used excessively during the first calcination to prepare the core substrate. As a result, the core substrate did not have the nickel oxide impurity phase, but the residual alkali was high. After adding a cobalt source for second calcination coating, the nickel oxide impurity phase disappeared, and the residual alkali content decreased slightly but was still high.
[0258] After sintering, Comparative Examples 2, 3, and 9 still showed obvious nickel oxide impurities. This indicates that when the coating amount was too high (x = 0.04) (Comparative Example 2), the nickel oxide impurities were too numerous in the core substrate, so even sintering could not eliminate them. When the cathode material did not contain Cu and the composition did not meet the requirements (Comparative Example 3), the impurities could not be effectively eliminated. When the sodium in the core substrate was not excessive (Comparative Example 9), even with the addition of a cobalt source for sintering, the nickel impurities could not be eliminated.
[0259] Furthermore, comparisons of Example 1 with Comparative Examples 1 and 7-10, Example 2 with Comparative Example 2, Example 3 with Comparative Example 3, Example 4 with Comparative Example 4, and Example 5 with Comparative Example 5 demonstrate that when the cathode material has the defined composition, including the defined overall composition, coating composition, and molar ratio of coating to core, the resulting cathode material exhibits excellent electronic conductivity and can achieve improved 0.1C initial discharge capacity and improved 1C high-temperature 45°C cycling performance.
[0260]
[0261] Table 2 shows the percentage of the main elements Ni, Co, Mn, and Cu in the surface (coating layer) of the cathode materials prepared in Examples 1-7, obtained by EDS analysis, as a percentage of the total atomic number of each element. The results in Table 2 show that the molar ratio of Ni to Co in the coating layer is approximately 1:1, and the percentage of each element basically satisfies the Na₂Ni... 1+y Co 1- y A α O 4+β The composition of.
[0262] Table 2
[0263]
[0264] The above description is merely an exemplary embodiment of the present invention. It should be noted that those skilled in the art can make improvements to the present invention without departing from the inventive concept, and all such improvements fall within the scope of protection of the present invention.
Claims
1. Positive electrode materials for sodium-ion batteries, including: A layered oxide core and a layered oxide coating layer formed on the core. The positive electrode material has the following overall composition: So 1+2x Ni u+x(1+y) Co x(1-y) M 1-u O 2+δ The covering layer is represented by the following formula: Na2Ni 1+y Co 1-y A α O 4+β And the molar ratio of the coating layer to the core is x. in x=0.01-0.03, u=0.40-0.49, y = -0.10 to 0.10, M is selected from at least two elements chosen from the metallic elements Cu, Fe, Mn, Ti, Mg, Zn, Li, Al, Ca, Zr, Ta, Mo, W, La, Sr, Sb, Ce, Nb, Sn, and Y, and includes Cu and Mn. δ = -0.40 to 0.40 A is selected from some or all of the elements of M. 0<α<1, 0<β<2。 2. The cathode material according to claim 1, wherein y = -0.05 to 0.
05.
3. The cathode material according to any one of claims 1-2, wherein M is at least two elements selected from the metallic elements Cu, Fe, Mn, Ti, Mg, Zn, Al, Zr, Sn, and Y.
4. The cathode material according to any one of claims 1-2, wherein M includes Cu, Mn and Ti.
5. The cathode material according to any one of claims 1-2, wherein element A and element M are the same.
6. The cathode material according to any one of claims 1-2, wherein the subscript of Mn element is 0.30-0.59, the subscript of Cu element is 0.01-0.20, and the subscript of Ti element is 0-0.20 in the overall composition formula of the cathode material.
7. The cathode material according to any one of claims 1-2, wherein the X-ray diffraction spectrum of the cathode material does not show a NiO peak.
8. The cathode material according to any one of claims 1-2, wherein the core has the following composition: Pretty u M 1-u-αx O 2+γ in: u, α, and x are as defined in claim 1; and γ = -0.40 to 0.
40.
9. The cathode material according to any one of claims 1-2, wherein the residual alkali content of the cathode material is less than 0.5%.
10. The cathode material according to any one of claims 1-2, wherein the core is an O3 phase structure and the coating layer is an O3 phase structure.
11. The cathode material according to any one of claims 1-2, wherein the cathode material has a Dv50 particle size of 1-100 μm.
12. The cathode material according to claim 1, wherein y = -0.02 to 0.
02.
13. The cathode material according to claim 1, wherein y = 0.
14. The cathode material according to claim 6, wherein the subscript of the Mn element in the overall composition formula of the cathode material is 0.40-0.
51.
15. The cathode material according to claim 6, wherein the subscript of Cu element in the overall composition formula of the cathode material is 0.01-0.
10.
16. The cathode material according to claim 6, wherein the subscript of the Ti element in the overall composition formula of the cathode material is 0.01-0.
10.
17. The cathode material according to any one of claims 1-2, wherein the residual alkali content of the cathode material is 0.1-0.5%.
18. The cathode material according to any one of claims 1-2, wherein the residual alkali content of the cathode material is 0.1-0.4%.
19. The cathode material according to any one of claims 1-2, wherein the cathode material has a Dv50 particle size of 5-20 μm.
20. A method for preparing a positive electrode material for a sodium-ion battery according to any one of claims 1-19, comprising the following steps: Core preparation: Na source, Ni source and M source are mixed uniformly according to the molar ratio of Na, Ni and M elements (1+2x):(u+x(1+y)):(1-u), and a first sintering is performed at a first temperature of 850-1000℃ in an oxygen-containing atmosphere. After cooling, the mixture is optionally crushed and sieved to obtain the core substrate, wherein the Na source and Ni source are in molar excess of 2x and x(1+y) respectively relative to the stoichiometry of the core composition. and Preparation of the coating layer: The prepared core substrate and Co source are uniformly mixed according to the molar ratio of excess Ni element to Co element in the core preparation as (1+y) / (1-y). Then, the mixture is sintered in an oxygen-containing atmosphere at a second temperature of 800-980°C, which is lower than the first temperature. After cooling, the mixture is optionally crushed and sieved to obtain the cathode material.
21. The method of claim 20, wherein The Na source is one or more compounds selected from the following: sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium oxalate, sodium hydroxide, sodium chloride, sodium sulfate, and sodium oxide; The Ni source is one or more compounds selected from the following: nickel carbonate, nickel nitrate, nickel acetate, nickel oxalate, nickel hydroxide, nickel sulfate, nickel chloride, nickel oxide, nickel manganese hydroxide, and nickel manganese titanium copper carbonate. The source M is provided in the form of carbonates, nitrates, sulfates, oxalates, acetates, chlorides, hydroxides, oxides, or combinations thereof of element M; and The cobalt source is one or more compounds selected from the following: cobalt carbonate, cobalt nitrate, cobalt acetate, cobalt oxalate, cobalt hydroxide, cobalt sulfate, cobalt chloride, and cobalt oxide.
22. The method according to any one of claims 20-21, wherein the first sintering is performed for 10-48 hours and the second sintering is performed for 10-48 hours.
23. The method according to any one of claims 20-21, wherein the second temperature is 10-150°C lower than the first temperature.
24. The method of claim 22, wherein the first sintering is performed for 10-30 hours.
25. The method according to claim 22, wherein the second sintering is carried out for 10-30 hours.
26. The method according to any one of claims 20-21, wherein the second temperature is 20-100°C lower than the first temperature.
27. A positive electrode composition for use in sodium-ion secondary batteries, comprising the positive electrode material for sodium-ion batteries according to any one of claims 1-19.
28. A sodium-ion secondary battery comprising the positive electrode composition according to claim 27.
29. The use of the sodium-ion secondary battery as described in claim 28 in energy storage devices for solar power generation, wind power generation, smart grid peak shaving, distributed power stations, backup power supplies, or communication base stations.
Citation Information
Patent Citations
Coated modified sodium ion layered positive electrode material and preparation method thereof
CN116314704A
Cobalt-coated layered sodium ion battery positive electrode material and preparation method thereof
CN118619371A